Work-Related Musculoskeletal Disorders in Dentistry: A Narrative Review - Ankita Gupta; Ami Rawal (Journal of Orofacial Research, 2022)
Work-related musculoskeletal disorders (WRMSDs) is very prevalent in dentistry. Physically and mentally, dentistry is a demanding job due to its time-consuming treatment procedures and mental pressure of the patients. Moreover, this Sars-Cov2 pandemic has brought a more risk to the dentist, thereby using more additional devices such as personal protection kits for their prevention which further limits the freedom of movements, increases mental stress, and imbalanced postures, and hence contributes more towards WRMSDs. These WRMSDs among dentists can be prevented or minimized by the use of ergonomic principles. The present review article discusses the various risk factors and methods of prevention of these WRMSDs.